2012
DOI: 10.4161/hv.8.1.17623
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for quadrivalent influenza vaccines

Abstract: Two antigenically distinct lineages of influenza B viruses have circulated globally since 1985. However, licensed trivalent seasonal influenza vaccines contain antigens from only a single influenza B virus and thus provide limited immunity against circulating influenza B strains of the lineage not present in the vaccine. In recent years, predictions about which B lineage will predominate in an upcoming influenza season have been no better than chance alone, correct in only 5 of the 10 seasons from 2001 to 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
303
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(326 citation statements)
references
References 24 publications
13
303
0
10
Order By: Relevance
“…This result is lower than reported in the United States (46%, from 2001/2002 to 2010/2011 seasons) and the Europe (58%, between 2003/2004 and 2010/2011 seasons) 18. Again, this varies by regions and influenza season globally 14, 18…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This result is lower than reported in the United States (46%, from 2001/2002 to 2010/2011 seasons) and the Europe (58%, between 2003/2004 and 2010/2011 seasons) 18. Again, this varies by regions and influenza season globally 14, 18…”
Section: Discussionmentioning
confidence: 71%
“…These two lineages of influenza B are antigenically and genetically different and studies in ferrets found no cross‐reactivity between the two strains 16. In recent decades, both lineages have cocirculated with varying relative intensity in the same season in many parts of the world including Australia 17, 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Type C strain infections are usually regarded as very mild and uncommon although outbreaks of symptomatic disease have been described and sero-prevalence studies suggest widespread infection among some populations. 9 Due to their generally mild nature, C virus types are not included in the currently available influenza vaccines.…”
Section: Influenza Diseasementioning
confidence: 99%
“…Although public health agencies continued to recommend the influenza B lineage thought most likely to prevail in the upcoming influenza season, the predominant circulating strain often was different from the recommended strain, indicating a need for development of a vaccine that would provide protection against both types of influenza B 15, 16. At the present time, four quadrivalent influenza vaccines have been licensed in the United States: FluMist Quadrivalent ® (MedImmune—2012), Fluarix Quadrivalent ® (GSK – 2012), Fluzone Quadrivalent ® (Sanofi Pasteur—2013), and FluLaval Quadrivalent ® (IDB—2013).…”
Section: Regulatory Experience and Challenges With New And Novel Inflmentioning
confidence: 99%